In vitro evaluation of Biosilicate® dissolution on dentin surface: a SEM analysis - Pinheiro, Michele Carolina [UNESP]; Lopes, Beatriz Maria Valério [UNESP]; Cavassim, Rodrigo [UNESP]; Pinto, Shelon Cristina Souza [UNESP]; Sampaio, José Eduardo Cezar [UNESP] (Universidade Estadual Paulista Júlio de Mesquita Filho, 2013)
INTRODUCTION: Biomaterials such as bioactive glasses and glass-ceramics have been proposed for the treatment of dentinal hypersensitivity. OBJECTIVE: to evaluate by scanning electron microscopy (SEM), the dissolution of a novel bioactive glass-ceramic (Biosilicate® 1-20 µm particles) on dentin surface samples, with different application methods and different dilution medium used for applying Biosilicate®. MATERIAL AND METHOD: 280 dentin samples were randomly divided into four groups: (1) Biosilicate® plus fluoride gel applied with Robinson brush; (2) Biosilicate® plus fluoride gel applied with microbrush; (3) Biosilicate® plus distilled water applied with Robinson brush; (4) Biosilicate® plus distilled water applied with microbrush. After treatment, the samples were immersed in saliva at different periods (0, 15 and 30 minutes, 1, 2, 12 and 24 hours). Two photomicrographs were obtained from each sample and were further analyzed by a blind calibrated examiner according to a Particle Dissolution Index created for this study. RESULT: The data were analyzed using the Mann-Whitney, Kruskal-Wallis and Dunn's tests. There was no statistical difference among the degrees of dissolution between the 4 groups in any period. CONCLUSION: Biosilicate® can be incorporated in both substances without differences in the degree of dissolution of the particles in any of the evaluated periods and the application of dentine can be performed with both methods evaluated.

INTRODUÇÃO: Biomateriais, tais como vidros bioativos e vidros cerâmicos têm sido propostos para o tratamento da hipersensibilidade dentinária. OBJETIVO: Avaliar por microscopia eletrônica de varredura (SEM), a dissolução de uma nova vitrocerâmica bioativa (Biosilicato®, partículas de 1-20 µm) na superfície de amostras de dentina, com diferentes métodos de aplicação e de meio de diluição diferente, usado para aplicação de Biosilicato®. MATERIAL E MÉtODO: 280 amostras de dentina foram divididas aleatoriamente em quatro grupos: (1) Biosilicato® mais flúor gel aplicado com escova de Robinson, (2) Biosilicato® mais flúor gel aplicado com microbrush, (3) Biosilicato® mais água destilada aplicado com escova de Robinson; (4) Biosilicato® mais água destilada aplicado com microbrush. Após o tratamento, as amostras foram imersas em saliva, em diferentes períodos (0, 30 e 15 minutos, 1, 2, 12 e 24 horas). Duas fotomicrografias foram obtidas a partir de cada amostra e foram analisadas por um examinador calibrado cego de acordo com um Índice de Dissolução de Partículas, criado para este estudo. RESULTADO: Os dados foram analisados usando o teste de Mann-Whitney, Kruskal-Wallis e Dunn. Não houve diferença estatística entre os graus de dissolução entre os quatro grupos em qualquer período. CONCLUSÃO: Biosilicato® pode ser incorporado em ambas às substâncias, sem diferenças no grau de dissolução das partículas em qualquer dos períodos de avaliação e a aplicação sobre da dentina pode ser realizada com os dois métodos avaliados.
Avaliação in vitro da dissolução do Biosilicato® sobre a superfície dentinária: análise por meio da microscopia eletrônica de varredura
Keywords: Biocompatible materials; dentin sensitivity; fluorine; Materiais biocompatíveis; sensibilidade da dentina; flúor